Improving physicochemical, mechanical, and biological properties of a porous polyvinyl alcohol/chitosan matrix via modification with magnesium and silicon agents - Nima Vakili; Azadeh Asefnejad; Mohammad Mohammadi; Hessam Rezaei; Amirsalar Khandan (Nanomedicine Journal, 2025)
Objective(s): Biocomposite scaffolds made from polymers and bioactive materials can provide the necessary bioactivity and mechanical properties for bone tissue engineering.Materials and Methods: In this study, we aimed to evaluate the properties of a novel composite scaffold made from a combination of chitosan, PVA, MgCl₂, and GPTMS as a crosslinking agent. Scanning Electron Microscopy (SEM) and Fourier-Transform Infrared Spectroscopy (FTIR) analysis characterized the prepared composite scaffold. The composite scaffolds' mechanical properties, bioactivity, biocompatibility, swelling, and degradation were also investigated.Results: Significant improvements in the mechanical properties were observed in the modified composite compared to those seen in the scaffold without MgCl₂. With an increase in MgCl₂ content, the scaffold's degradation and porosity increased, while its swelling capacity decreased. Bioactivity was also enhanced in the composite following the further addition of MgCl₂.Conclusion:  In vitro tests for cytotoxicity and MG-63 cell proliferation showed that the composite scaffolds were non-cytotoxic, resulting in better cell adherence and growth on the surface of these scaffolds.